1995
DOI: 10.1002/jpln.19951580302
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of ammonia emission after liquid manure application: II. Comparison of the wind tunnel and the IHF method under field conditions

Abstract: A wind tunnel was constructed for measurement of NH3− N volatilization after application of liquid manure. It combines the advantages of micrometeorological field methods with those of customary wind tunnel methods. The wind tunnel, as specified in part I (Braschkat et al., 1993), is characterized by: ‐the same (or higher) reliability of results as in field measurement by the IHF method (Integrated Horizontal Flux, also known as Mass Balance) ‐universal applicability independent of topographical conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Such a course with the main part of emissions occurring in the first ten to twenty hours is quite common after slurry spreading and has often been documented (e.g. Pain et al, 1989;Mannheim et al, 1995;Braschkat et al, 1997;Génermont et al, 1998;Menzi et al, 1998;Misselbrook et al, 2002;Huijsmans et al, 2003;Rochette et al, 2008;Sanz et al, 2010). The conditions at the Oensingen grassland revert back to a small, potentially bi-directional flux regime after about 5 days and even the canopy compensation point returns to prefertilisation levels after about 10 days .…”
Section: Dynamics Of Nh 3 Volatilisationmentioning
confidence: 88%
“…Such a course with the main part of emissions occurring in the first ten to twenty hours is quite common after slurry spreading and has often been documented (e.g. Pain et al, 1989;Mannheim et al, 1995;Braschkat et al, 1997;Génermont et al, 1998;Menzi et al, 1998;Misselbrook et al, 2002;Huijsmans et al, 2003;Rochette et al, 2008;Sanz et al, 2010). The conditions at the Oensingen grassland revert back to a small, potentially bi-directional flux regime after about 5 days and even the canopy compensation point returns to prefertilisation levels after about 10 days .…”
Section: Dynamics Of Nh 3 Volatilisationmentioning
confidence: 88%
“…All treatments showed maximum volatilization rate during the measurement period immediately following application, with a subsequent decrease of the rate to low NH, release during the night (1 1-19 hours after application). High NH, volatilization rates soon after slurry application are quite common (Amberger, 1990, Horlacher & Marschner, 1990, Mannheim et al, 1995. The highest volatilization rate measured during this experiment (untreated, broadcast slurry in dry weather) reached 210 pg NH,-N m-' s-I, corresponding to nearly 8 kg NH,-N ha-' h-' or a loss of 48% of TAN from applied slurry during the first 3.5 hours.…”
Section: Main Experimentsmentioning
confidence: 92%
“…57 Enclosures left on-site during rainfall will overestimate . 51 Also, enclosure application is limited in tall crops.…”
Section: Important Enclosure Studiesmentioning
confidence: 99%
“…Hence, given its adverse impacts, and the need for mitigation at the regional, national, and global scales, ammonia is regarded by the National Research Council as the main constituent of concern present in emissions originating from animal feeding operations. 2 The 1998 ammonia inventory in the United Kingdom showed that land application of animal waste and grazing (cattle only) accounted for 51,26, and 33% of ammonia emissions from cattle, swine, and poultry productions, respectively; corresponding ammonia losses from waste storage were 13, 10, and Ͻ1%, respectively. 3 Whereas ammonia emissions data from specific components of the animal waste management system are not yet available for the United States, ammonia losses from land and liquid surfaces may constitute a substantial fraction of total loadings given that agriculture accounts for 87% of the total U.S. atmospheric ammonia loading.…”
Section: Introductionmentioning
confidence: 99%